Karakteristik Siswa Sekolah Dasar Kelas Rendah - Suroto, Suroto (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2024)
This article aims to examine the characteristics of low-grade elementary school students. Characteristic is a term that is often used in a variety of contexts, both in everyday life and in the field of science. Characteristics can refer to distinctive traits or traits that distinguish an object, individual, or phenomenon from others. Lower grade students are students who are in levels one, two, and three with an age range of 6-9 years while for high grade students are at the fourth, fifth and sixth grade levels with an age range of 9-13 years. Lower grade students can be categorized in the early childhood group. Low-grade Elementary School Students have different characteristics from high-grade Elementary School Students. Characteristics of low grade Primary School Students include: there is a strong relationship between physical condition and school performance; likes to praise yourself; if he is unable to complete a task or work, the task or work is considered unimportant; likes to compare himself with other children, if it benefits him; and likes to belittle others.